Chasing Shadows: The Uses of Photography in the Work of Second-Generation Visual Artists in the UK. Issue 1 (1st March 2023) - Bohm-Duchen, Monica
Abstract: Drawing on the influential concept of postmemory first mooted by Marianne Hirsch, and on the links between photography and mortality first explored by Susan Sontag and Roland Barthes, this article analyses the work of ten largely UK-based visual artists who, as members of the so-called second generation (namely, the descendants of Holocaust survivors and refugees), make use of the photographic medium to engage creatively and conceptually – and often in a conspicuously gendered way – with the legacy of their families' traumatic histories. Some of the artists (Halter, Tucker) base their handcrafted imagery directly on pre-war family photographs; others (Winckler, Brunstein, Petzal, Gorney, Kerr, Davidmann) incorporate actual photographs, past and present, into mixed media artworks, frequently manipulating and even doing violence to them. Others again (Garbasz) use photographs taken in the present to reach out to an inaccessible past, while yet others (Markiewicz) employ a more abstract and allusive approach to the medium.